2016
DOI: 10.1155/2016/4931502
|View full text |Cite
|
Sign up to set email alerts
|

The Segmentation of Wear Particles Images UsingJ-Segmentation Algorithm

Abstract: This study aims to use a JSEG algorithm to segment the wear particle’s image. Wear particles provide detailed information about the wear processes taking place between mechanical components. Autosegmentation of their images is key to intelligent classification system. This study examined whether this algorithm can be used in particles’ image segmentation. Different scales have been tested. Compared with traditional thresholding along with edge detector, the JSEG algorithm showed promising result. It offers a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…For example, Wang et al [13] combined the watershed algorithm with an improved ant colony clustering algorithm to achieve accurate segmentation of wear debris images. Liu et al [14] employed the unsupervised segmentation of colortexture regions in images and a video algorithm to segment a wear debris image, and they suggested that the method outperforms standard threshold segmentation and edge detection.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wang et al [13] combined the watershed algorithm with an improved ant colony clustering algorithm to achieve accurate segmentation of wear debris images. Liu et al [14] employed the unsupervised segmentation of colortexture regions in images and a video algorithm to segment a wear debris image, and they suggested that the method outperforms standard threshold segmentation and edge detection.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yu et al [ 26 ] used background subtraction methods to segment wear particles, allowing them to quantify the wear of pivot bearings. Liu et al [ 27 ] used the JPEG segmentation algorithm (JSEG) [ 28 ] to segment wear particles in ferrographic images. More recently, Wang et al [ 29 ] used CNNs to classify, quantify, and register wear debris.…”
Section: Introductionmentioning
confidence: 99%
“…The quantity of wear particles and their morphology consequently accelerate the process and the intensity of wear (Kučera et al, 2016;Sejkorová and Glos, 2017). Wear particle analysis helps to assess the condition of the machinery and reliability in mechanical systems (Liu et al, 2016;Peng et al, 2015). The wear process results in generation of particles of various size, shape, quality and morphology (Akchurin et al, 2016;Hönig and Orsák, 2016;Wäsche et al, 2015).…”
mentioning
confidence: 99%